Empreendedorismo na gestão de empresas criadas por necessidade - Cimadon, José Eduardo (2008)
The trade of creating companies is inherent to the entrepreneurs. However, many of them create the enterprises by necessity, making the difficulty of their management potential. In this paper, it is aimed to know, understand and share the learning of entrepreneurs who overcame these difficulties. Theoretically after the works of Dolabela, Filion, Baron & Shane and Stenberg who deal with the entrepreneurial processes. And, pragmatically, with the case study of entrepreneurs by necessities, who have created enterprises, developed entrepreneur characteristics and succeeded. From the synthesis of these theories and practices, it is emerged a standard of an entrepreneur performance that, it is intended, guides other entrepreneurs who are in a similar situation. Orientated by theories, the interviewer listened, compiled, related and commented the deposition of interviewed entrepreneurs. In the end, it has been noticed that having their own business made them motivated, and the attention to the feedbacks and external stimulus has transformed them. Whereas developing entrepreneurial experiences, these people, influenced by different standards of performance, have had their own standards altered. The information analysis advises about the fact of entrepreneurial process has been developed and it was established after the experiences lived by these entrepreneurs, as well as the events which are mentioned in the theories. It may be said that their attitudes have catalyzed the changes, which are characterized by coherence and assertiveness.